Efficacy Of Ultraviolet Irradiation For Sterilization Of Dental Instrumen Against Oral Microbiome Growth - Afrohhatunnisa, Khossy’; Aryati Eko Ningtyas, Endah; Prasko, Prasko; Benyamin, Benny (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2024)
Background: Oral microbiome bacteria can attach to a variety of surfaces including oral diagnostic devices. Oral diagnostic tools that are not properly cleaned and sterilized can be used as a place for bacteria to multiply and cause cross-infection. Objective: This research aims to test the success of sterilization equipment using Ultraviolet light to sterilize dental instruments when used for dental examination activities in the field. Methods:Â Randomized Experimental laboratory Pretest Posttest with Control Group Design. The subject of the study was the mouth glasses used after dental examination at UKGS. The intervention of the mouth glass was sterilized using Ultraviolet-c at three different times, namely 20 minutes, 25 minutes, and 30 minutes. Results: The results of Ultraviolet-c with One Way Anova test results showed a p-value of 0.000 (p<0.05) indicating a significant difference in the number of oral microbiome bacteria between sterilization time and the number of oral microbiome bacterial colonies. Pearson correlation test p-value (p<0.05) it can be concluded that there is a significant relationship between sterilization time and the number of oral microbiome colonies with a correlation coefficient of -0.850 which means that the longer the sterilization time, the number of oral microbiome bacteria decreases. Conclusion: Ultraviolet-c for 30 minutes is effective for sterilization of oral microbiome bacteria.